Pengaruh Harga, Store Atmosphere, Dan Kualitas Pelayanan Terhadap Revisit Intention Di Halona X Van Geluk Coffee & Resto - Izhagi Rizkidona; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
The subject of this study is the revisit intention at Halona X Van Geluk Coffee & Resto. Pre-research data indicates that the low desire of visitors to return to the place is caused by factors such as price, store atmosphere, and service quality. The aim of this research is to identify the reasons behind these findings. This quantitative descriptive research employs purposive sampling, involving 170 respondents who answered a questionnaire. The questionnaire's validity was tested using a Likert scale. The t-test results indicate that the variable of price (X1) has a significance level of 0.000, which is below 0.05, suggesting a significant influence of price on the revisit intention. Similarly, the store atmosphere variable (X2) also has a significance level of 0.000, below 0.05, indicating a significant influence of store atmosphere on the revisit intention